2021
DOI: 10.4049/jimmunol.2100379
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIR Genes and MHC Class I Ligands with Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic illness that is associated with immune dysregulation. NK cell function has previously been associated with AD. NK cells directly interact with polymorphic HLA class I ligand variants using killer cell Ig-like receptors (KIRs). The purpose of this study was to identify potential associations between NK cell function and AD by evaluating variation in the presence of KIR genes as well as KIR gene interactions with the appropriate HLA class I KIR–specific ligands. Human DNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 69 publications
3
27
0
Order By: Relevance
“…18,20,21 We have recently shown that the KIR genes KIR2DL5, KIR2DS5, and KIR2DS1 are more frequently found in individuals with AD. 22 This is also true for the HLA-C2 epitope and HLA-B*-21T leader sequence. 22 The goal of this study was to examine allelic variation in previously associated KIR genes KIR2DL5, KIR2DS5, and KIR2DS1 with AD.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…18,20,21 We have recently shown that the KIR genes KIR2DL5, KIR2DS5, and KIR2DS1 are more frequently found in individuals with AD. 22 This is also true for the HLA-C2 epitope and HLA-B*-21T leader sequence. 22 The goal of this study was to examine allelic variation in previously associated KIR genes KIR2DL5, KIR2DS5, and KIR2DS1 with AD.…”
Section: Introductionmentioning
confidence: 92%
“…22 This is also true for the HLA-C2 epitope and HLA-B*-21T leader sequence. 22 The goal of this study was to examine allelic variation in previously associated KIR genes KIR2DL5, KIR2DS5, and KIR2DS1 with AD. This investigation is important in that previous studies have shown that KIR association with diseases such as HIV and preeclampsia is highly dependent on allelic variation and cell surface expression also varies signi cantly by KIR allotype.…”
Section: Introductionmentioning
confidence: 92%
“…One of the most recently identified examples is atopic dermatitis, in which distinct compound genotypes associate, respectively, with susceptibility and progression of disease. [175][176][177] These types of relationships are likely to be recapitulated in further immune-mediated diseases such as multiple sclerosis, which has established associations with KIR and HLA combinatorial diversity. 175,178 The recent confirmation that multiple sclerosis is triggered by EBV infection 179,180 places cytotoxic immune effector cells in context of both initiation and progression of the disease.…”
Section: Kir/hla In Autoimmunitymentioning
confidence: 99%
“…KIR and HLA-C ligands have also been associated with the development of endometriosis ( Chou et al., 2020 ). A recent study revealed that KIR gene variation is associated with AD ( Margolis et al., 2021 ). Because NK cell function and KIR genes appear to be involved in the pathogenesis of AD, preeclampsia, and endometriosis, it is possible that there may be an association between these conditions.…”
mentioning
confidence: 99%
“…The findings of our work and others support that nonallergic illnesses are also associated with AD ( Sinaii et al., 2002 ; Stokholm et al., 2017 ). Furthermore, the associations with preeclampsia and endometriosis are potentially related to genetic variation in KIR genes and NK cell function, revealing additional immunologic pathways that may be associated with AD ( Margolis et al., 2021 ; Nakimuli et al., 2015 ).…”
mentioning
confidence: 99%